2018
DOI: 10.1080/17441692.2018.1514418
|View full text |Cite
|
Sign up to set email alerts
|

Are treatment supporters relevant in long-term Antiretroviral Therapy (ART) adherence? Experiences from a long-term ART cohort in Uganda

Abstract: Treatment supporters remain important in adherence to long-term ART. HIV-care providers need to encourage the involvement of a treatment supporter for individuals taking ART long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 54 publications
(65 reference statements)
1
33
0
Order By: Relevance
“…In addition, HIV care medications including ART and cotrimoxazole were always in stock and people living with HIV were offered ART adherence health education. During the pre-ART initiation health education sessions, participants and their treatment supporters were prepared for ART initiation [42]. Continuous post ART initiation health education was offered to people living with HIV at every ART refill visit to encourage them to adopt safe sexual behaviours and adherence to ART.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, HIV care medications including ART and cotrimoxazole were always in stock and people living with HIV were offered ART adherence health education. During the pre-ART initiation health education sessions, participants and their treatment supporters were prepared for ART initiation [42]. Continuous post ART initiation health education was offered to people living with HIV at every ART refill visit to encourage them to adopt safe sexual behaviours and adherence to ART.…”
Section: Methodsmentioning
confidence: 99%
“…The current crisis because of COVID-19 creates all the conditions that have been indicated in previous studies as being associated with HIV and TB treatment non-adherence and lost to follow across the continent. 25,49,[58][59][60][61][62][63][64][65][66][67] The cost-effectiveness of various innovative solutions for service delivery is well documented across the continent, 54,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] warranting their utility to mitigate the risks posed by COVID-19 (Table 3); however, some constraints have been reported. In relation to mobile clinics, these include logistical challenges as well as spatial and structural constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Travel restrictions and social distancing may also disrupt the existing community-based ART delivery and psychosocial support strategies that mitigate the negative impacts of barriers to ART adherence (e.g., psychological distress, community stigma, and distance from health care centers) and provide effective ART uptake reminders to PLWH [12]. By impeding PLWH's ability access to ART medication at community venues or by preventing community health workers from making home visits to conduct health and social needs assessments and deliver ART medication [13][14][15][16][17], COVID-19 prevention efforts may come at the cost of PLWH's physical and psychosocial health.…”
Section: Impeding Access To Community-based Supportmentioning
confidence: 99%
“…Treatment supporters offer one cost-effective and COVID-19-compliant means of providing community-based ART adherence support and care for PLWHs. Nominated by patients or health care providers, treatment supporters are typically PLWH's confidantes (e.g., close relatives, parents, or partners) who have the moral authority to help them with ART management and provide psychosocial support [14][15][16]. A recent systematic review found that treatment supporter interventions in SSA significantly improved ART adherence and virologic suppression among adult PLWHs compared to the standard of care [16].…”
Section: Treatment Supportersmentioning
confidence: 99%
See 1 more Smart Citation